THE STUDY OF FLUX REDISTRIBUTION DURING MOLECULAR PHOTODISSOCIATION - ADIABATIC AND DIABATIC ANALYSES AND APPLICATION TO THE DISSOCIATION OF CH3I - Alexander, M; Rist, C; Manolopoulos, D (1992)
This paper extends our new method for the study of the mechanism of molecular photodissociation. This method involves the time-independent study of the growth of photofragment flux, governed by photon absorption, and the subsequent redistribution of the flux, governed by the Hamiltonian in the excited, unbound state. The flux analysis can be carried out easily in either a diabatic (asymptotic), locally adiabatic, or fully adiabatic basis. The redistribution of the photofragment flux can be investigated in either internal state space or coordinate space at each excitation energy. Application is made to one- and two-dimensional models for the photodissociation of CH3I. © 1992 American Institute of Physics.